2015
DOI: 10.11646/phytotaxa.208.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Auricularia thailandica sp. nov. (Auriculariaceae, Auriculariales) a widely distributed species from Southeastern Asia

Abstract: Auricularia is an important genus among the jelly fungi due to its popular consumption and medicinal properties. A new species of Auricularia, A. thailandica is described from fresh collections made from the Philippines, Thailand and Southern China based on morphological and molecular characters. Auricularia thailandica differs from other species by having short and loosely arranged abhymenial hairs on the basidiomata and in the different size of the zones in a cross section of the basidiomata. The species is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Auricularia thailandica Bandara & K.D. Hyde was recently described from Thailand by Bandara et al [24], and it is very close to A. fibrillifera both in morphology and phylogeny. Both species occur in Southeast Asia and it is very difficult to distinguish them by morphology, especially the dry basidiomata.…”
Section: Taxonomymentioning
confidence: 96%
See 2 more Smart Citations
“…Auricularia thailandica Bandara & K.D. Hyde was recently described from Thailand by Bandara et al [24], and it is very close to A. fibrillifera both in morphology and phylogeny. Both species occur in Southeast Asia and it is very difficult to distinguish them by morphology, especially the dry basidiomata.…”
Section: Taxonomymentioning
confidence: 96%
“…An additional ten new species, including A. [22][23][24][25][26]. In addition, the phylogenetic analysis based on nLSU sequences showed that Auricularia was polyphyletic [27][28][29], but the genus was shown to be monophyletic in recent multi-gene phylogenetic analyses based on ITS and nLSU sequences [30,31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With this phylogenetic frame as a main reference, the taxonomy and phylogeny of poroid and lamellate species were further explored (Miettinen et al 2012;Zhou and Dai 2013;Sotome et al 2014;Wu et al 2017;Spirin et al 2019a). In addition, the knowledge of the diversity of species with gelatinous basidiomes has been extremely enriched recently (Bandara et al 2015;Wu et al 2015a, b;Malysheva et al 2018;Spirin et al 2018Spirin et al , 2019bChen et al 2020;Ye et al 2020;Wang and Thorn 2021).…”
Section: Introductionmentioning
confidence: 99%
“…As a kind of edible and medicinal fungi, Auricularia mushrooms have been widely consumed all around the world. As the fourth most produced mushroom genera, Auricularia has been collected, cultivated and consumed in many countries, such as China, Japan, Vietnam and New Zealand, for hundreds of years (Bandara et al, 2015). Mounting studies have revealed a wide range of pharmacological functions of Auricularia and their derivatives.…”
Section: Introductionmentioning
confidence: 99%